Responsibility of the Director of a Limited Liability Company who has resigned from the implementation of the EGMS based on Law No. 40 of 2007 concerning Limited Liability Companies - Edward Venansius Mao Goa; Christine S.T. Kansil (International Journal of Social Sciences and Humanities, 2026)
Limited Liability Companies as a legal entity that adheres to a three-tier board system consisting of the General Meeting of Shareholders (GMS), the Board of Directors, and the Board of Commissioners require clear legal certainty regarding the division of authority and responsibility of each organ. One of the legal issues that often arise in practice is regarding the status and responsibilities of the Board of Directors who have submitted their resignation in relation to the holding of the Extraordinary General Meeting of Shareholders (EGMS). This study aims to analyze the legal responsibility of the Board of Directors who have resigned from the implementation of the EGMS and to examine the legal certainty for shareholders on the EGMS held by the Board of Directors during the transition period, based on Law Number 40 of 2007 concerning Limited Liability Companies. This study uses a normative legal research method with a statute approach and a case approach. The results of the study show that the resignation of the Board of Directors does not necessarily relieve the person concerned from his legal obligations and responsibilities. During the transition period until the GMS accepts or decides on the resignation, the Board of Directors remains obliged to carry out its duties, including facilitating the implementation of the EGMS; Negligence in this case can give rise to civil liability that cannot be avoided by taking refuge behind the doctrine of the Business Judgment Rule. Legal certainty for majority shareholders is realized through the guarantee of the validity of EGMS resolutions held by the Board of Directors during the transition period as long as all formal and procedural requirements are met, while legal certainty for minority shareholders is realized through protection instruments in the form of the right to sue for annulment of the GMS resolution, appraisal rights, and alternative EGMS implementation mechanisms through the Board of Commissioners or court determinations.